In vivo imaging methods to assess glaucomatous optic neuropathy. (December 2015) - Fortune, Brad
Abstract: The goal of this review is to summarize the most common imaging methods currently applied for in vivo assessment of ocular structure in animal models of experimental glaucoma with an emphasis on translational relevance to clinical studies of the human disease. The most common techniques in current use include optical coherence tomography and scanning laser ophthalmoscopy. In reviewing the application of these and other imaging modalities to study glaucomatous optic neuropathy, this article is organized into three major sections: 1) imaging the optic nerve head, 2) imaging the retinal nerve fiber layer and 3) imaging retinal ganglion cell soma and dendrites. The article concludes with a brief section on possible future directions. Highlights: Techniques currently in common use for in vivo assessment of ocular structure in experimental glaucoma include OCT and SLO. These and other imaging modalities also can be used in clinical studies to quantify aspects of glaucomatous optic neuropathy. By incorporating in vivo imaging into laboratory studies, fewer animals are required to achieve robust outcomes and translation. Recent developments hold extraordinary promise for revealing important events in glaucoma pathogenesis in living eyes.